Polio Eradication Initiative: Contribution to improved communicable diseases surveillance in WHO African region. Issue 43 (10th October 2016) - Mwengee, William; Okeibunor, Joseph; Poy, Alain; Shaba, Keith; Mbulu Kinuani, Leon; Minkoulou, Etienne; Yahaya, Ali; Gaturuku, Peter; Landoh, Dadja Essoya; Nsubuga, Peter; Salla, Mbaye; Mihigo, Richard; et al.
Highlights: PEI supported implementation of surveillance for other priority communicable diseases. PEI resources and infrastructure can be used as one strategy to build IDSR in Africa. Other disease-specific programs with eradication goals might consider investing IDSR. Abstract: Introduction: Since the launch of the Global Polio Eradication Initiative (GPEI) in 1988, there has been a tremendous progress in the reduction of cases of poliomyelitis. The world is on the verge of achieving global polio eradication and in May 2013, the 66th World Health Assembly endorsed the Polio Eradication and Endgame Strategic Plan (PEESP) 2013–2018. The plan provides a timeline for the completion of the GPEI by eliminating all paralytic polio due to both wild and vaccine-related polioviruses. Methods: We reviewed how GPEI supported communicable disease surveillance in seven of the eight countries that were documented as part of World Health Organization African Region best practices documentation. Data from WHO African region was also reviewed to analyze the performance of measles cases based surveillance. Results: All 7 countries (100%) which responded had integrated communicable diseases surveillance core functions with AFP surveillance. The difference is on the number of diseases included based on epidemiology of diseases in a particular country. The results showed that the polio eradication infrastructure has supported and improved the implementation of surveillance of other priority communicable diseases under integrated diseases surveillance and response strategy. Conclusion: As we approach polio eradication, polio-eradication initiative staff, financial resources, and infrastructure can be used as one strategy to build IDSR in Africa. As we are now focusing on measles and rubella elimination by the year 2020, other disease-specific programs having similar goals of eradicating and eliminating diseases like malaria, might consider investing in general infectious disease surveillance following the polio example.